Absence of VLDL secretion does not affect α-tocopherol content in peripheral tissues - Kaori Minehira-Castelli (Journal of Lipid Research, 2006)
α-Tocopherol is a lipid-soluble antioxidant that helps to prevent oxidative damage to cellular lipids. α-Tocopherol is absorbed by the intestine and is taken up and retained by the liver; it is widely presumed that α-tocopherol is then delivered to peripheral tissues by the secretion of VLDL. To determine whether VLDL secretion is truly important for the delivery of α-tocopherol to peripheral tissues, we examined α-tocopherol metabolism in mice that lack microsomal triglyceride transfer protein (Mttp) expression in the liver and therefore cannot secrete VLDL (MttpΔ/Δ mice). MttpΔ/Δ mice have low plasma lipid levels and increased stores of lipids in the liver. Similarly, α-tocopherol levels in the plasma were lower in MttpΔ/Δ mice than in controls, whereas hepatic α-tocopherol stores were higher. However, α-tocopherol levels in the peripheral tissues of MttpΔ/Δ mice were nearly identical to those of control mice, suggesting that VLDL secretion is not critical for the delivery of α-tocopherol to peripheral tissues. When fed a diet containing deuterated α-tocopherol, MttpΔ/Δ and control mice had similar incorporation of deuterated α-tocopherol into plasma and various peripheral tissues. We conclude that the absence of VLDL secretion has little effect on the stores of α-tocopherol in peripheral tissues, at least in the mouse.